Sosialisasi Dan Peningkatan Pengetahuan Tentang Bahaya Tindak Pidana Perdagangan Orang (TPPO) Di Asia Tenggara Kepada Masyarakat Indonesia Yang Bermukim di Thailand - Muhammad Fathun, Laode; Mulyawati Murni, Melissa; Setiawan, Asep (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2026)
Human trafficking in the ASEAN region remains a serious transnational challenge, particularly involving Indonesian citizens (WNI) and Indonesian migrant workers (PMI) in Thailand. Limited safe migration literacy, inadequate skills, the use of non-procedural migration channels, and the growing prevalence of digitally facilitated exploitation increase the vulnerability of PMI to trafficking in persons (TIP). This condition underscores the importance of prevention efforts grounded in education and public awareness strengthening. This socialization activity aimed to provide academic communities as well as Indonesian citizens and migrant workers in Thailand with a better understanding of the risks of TIP, lawful overseas employment procedures, and available protection and reporting mechanisms. The method employed consisted of online socialization and educational outreach conducted through a webinar collaboratively organized by the Indonesian Embassy in Bangkok, lecturer from Universitas Pembangunan Nasional Veteran Jakarta, and Pengurus Cabang Istimewa Muhammadiyah in Thailand (PCIM Thailand), involving approximately 40 participants from Indonesia and Thailand. The implementation of the activity functioned as a platform for information dissemination and interactive dialogue regarding recruitment patterns in trafficking cases, the importance of compliance with official overseas placement procedures, and the roles of government and civil society organizations in protecting migrant workers. This cross-sector collaborative socialization represents a contributive educational practice in strengthening the protection of Indonesian citizens abroad and highlights the importance of stakeholder synergy in addressing transnational trafficking issues.